SIPAKATAU SIPAKALEBBI SIPAKAINGGE SIPAKATOU SEBAGAI NILAI DASAR PENDIDIKAN KARAKTER - Yunus; Alfurqan; Ahmad Taufik Hidayat (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
The study explains the form of local wisdom of Bugis culture as a cultural value that is characteristic of the Palopo people. This type of research is qualitative. The local wisdom that develops in Palopo City is in line with the pluralistic Palopo culture that develops in Indonesia. Palopo city has local wisdom values such as humanizing (sipakatau), respecting (Sipakalebbi), remembering (Sipakingge'). These values are always preserved, so that they become the glue of religious harmony in Palopo City. The value of pluralism in the education of local wisdom, Bugis culture, embodies the concept of pesse as the value of Sipakatau, Sipakalebbi, Sipakingge, Sipakatou. Bugis culture has love and compassion for others shown by proverbs such as Mali siparappe, rebba sipatokkong, malilu sipakinge (others are swept away, helped, others fall, are helped to get up, others are out of the norm being reminded/reinforced). Palopo people value peace, love to help fellow human beings, especially if it is a fellow human being .